Algorithmic soft tissue femoral release in anterior approach total hip arthroplasty - Morad Chughtai, MD; Linsen T. Samuel, MD, MBA; Alexander J. Acuña, BS; Atul F. Kamath, MD (Arthroplasty Today, 2019)
Although the anterior approach for total hip arthroplasty has gained increasing utilization, some studies have suggested a higher risk of femoral complications, as well as difficulty with femoral exposure. Techniques of soft tissue releases have been described to offer better femoral exposure, and to help mitigate complications. The purpose of the study is to describe an algorithmic soft tissue femoral release in direct anterior approach total hip arthroplasty and to assess the clinical outcomes of patients upon which this algorithm of femoral soft tissue releases was utilized. Clinical outcomes with the Harris Hip Score, reoperation rates, component survivorship, and complications were analyzed. Keywords: Anterior approach, Soft tissue release, Total hip arthroplasty, Clinical outcomes, Femoral release, Component survivorship